2011
DOI: 10.1002/ijc.26143
|View full text |Cite
|
Sign up to set email alerts
|

The toll‐like receptor 2 (TLR2) ‐196 to ‐174 del/ins polymorphism affects viral loads and susceptibility to hepatocellular carcinoma in chronic hepatitis C

Abstract: Chronic hepatitis C virus (HCV) infection is a major risk factor for hepatocellular carcinoma (HCC). HCV proteins core and NS3 can bind to toll-like receptor 2 (TLR2) and trigger inflammatory responses. Polymorphisms in the TLR2 gene predispose to various forms of malignancy but have not been studied in HCV-associated HCC. Here, we investigated whether single nucleotide polymorphisms (SNPs), rs4696480, rs5743708, rs5743704 and the -196 to -174 del/ins polymorphism of the TLR2 gene affect the risk for HCC in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
37
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 24 publications
12
37
0
2
Order By: Relevance
“…In a study on neurocysticircosis (NCC), TLR4 Asp299Gly and Thr399Ile polymorphisms were associated with its occurrence (P < 0.001 for Asp299Gly; P = 0.003 for Thr399Ile) and progression to symptomatic NCC, compared with control subjects or asymptomatic NCC [20]. In another study, the frequency of the TLR2 196 -174 del allele was higher in patients with HCV-associated hepatocellular carcinoma (22.5%) than in HCV-infected patients without hepatocellular carcinoma (15.6%, P = 0.016) and healthy controls (15.3%, P = 0.003) [21]. Thus, association between genetic polymorphisms of innate immunity components and outcome might depend on the type of infection or pathogen involved.…”
Section: Discussionsupporting
confidence: 41%
“…In a study on neurocysticircosis (NCC), TLR4 Asp299Gly and Thr399Ile polymorphisms were associated with its occurrence (P < 0.001 for Asp299Gly; P = 0.003 for Thr399Ile) and progression to symptomatic NCC, compared with control subjects or asymptomatic NCC [20]. In another study, the frequency of the TLR2 196 -174 del allele was higher in patients with HCV-associated hepatocellular carcinoma (22.5%) than in HCV-infected patients without hepatocellular carcinoma (15.6%, P = 0.016) and healthy controls (15.3%, P = 0.003) [21]. Thus, association between genetic polymorphisms of innate immunity components and outcome might depend on the type of infection or pathogen involved.…”
Section: Discussionsupporting
confidence: 41%
“…As shown in Figure 1, a total of 14 studies were finally identified (Nieters et al, 2006;Etokebe et al, 2009;Purdue et al, 2009;Ashton et al, 2010;Balistreri et al, 2010;Gast et al, 2011;Zeng et al, 2011;Junjie et al, 2012;Kim et al, 2012;Nischalke et al, 2012;Slattery et al, 2012;Yang et al, 2012;Pimentel-Nunes et al, 2013). For the +597T>C polymorphism (rs3804099), 8 studies were available, including a total of 3987 cases and 5079 controls.…”
Section: Characteristics Of Studiessupporting
confidence: 48%
“…This substitution may significantly alter the function of the promoter, likely leading to decreased transcription of TLR2 (14). This polymorphism is reported to be associated with increased susceptibility to hepatocellular carcinoma and gastric cancer (15,16).…”
Section: Introductionsupporting
confidence: 46%